Morfološki in funkcionalni vidiki razvoja mladih športnikov - Figueiredo, A. J.; de Oliveira Matta, M.; Werneck, F. Z. (Kinesiologia Slovenica, 2014)
There is a strong link between maturational development and growth and performance. Organising age groups according to the criteria of chronological age leads to a big difference in size, composition and performance, and adolescence is the period when these differences are more visible with the ages between 13 and 15 years appearing to be the most heterogeneous period. In the same age group, maturationally more advanced subjects are generally heavier and taller than their peers of the same chronological age from childhood to the end of their adolescence. However, adults do not usually reveal the same differences when the same comparison is made. This situation can be explained by the catch up phenomenon in late-maturing individuals. The initial process for identifying promising athletes is multidimensional and the literature in the area shows that growth and maturation are two important concepts allowing a better understanding of the identification, selection and development processes of young athletes. Young soccer players tend to be above the mean for height and mass and tend to have an advanced biological maturity status with increasing age during adolescence and in elite development programmes. Worst results have been reported for body size and functional performance in young soccer players who were not selected to play in more demanding competitions or who had dropped out from sport. The same trend was visible in academy players who were not offered a professional contract. Despite the lack of evidence that at the beginning of the process the anthropometrical, maturational and physical characteristics are not directly associated with an exceptional performance in adulthood, it is of interest to understand that these indicators may open the doors of academies and other training centres of excellence promoting better conditions and better coaching for select players. Recently, decennial differences were not found in the entrance profile of soccer players in a club academy. This finding suggests that the sport (soccer) promotional strategies are being maintained despite the increased demandingness of professional players` anthropometric characteristics and the demands of actual professional soccer competitions.